KETERAMPILAN GURU DALAM MENGELOLA KELAS MENURUT ASMADAWATI - Sari, Dea Aulia; Octaviani, Furi; Putri, Puspita; Suswita, Nila (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2022)
Along with the times in the world of education, including when in the classroom, a teacher should have management that is good and unique, and easy to implement, with the condition that the teacher is capable, students are capable and not burdening the teacher, therefore classroom management must be organized and made in an appropriate manner. structured and consistent in its implementation, or in the sense of the word halves. Sometimes good management can lead students to successful learning. And the research method that the author uses is a literature study approach, which is sourced from book references, and others. Classroom management is an effort that is deliberately carried out in order to achieve teaching goals. The simple conclusion is that classroom management is a class management activity for the sake of teaching.